Introduction and Application Analysis of SDN in PTN - Jinkai Tang; Qi Zhang (Dianxin kexue)
With the features of end-to-end QoS, statistical multiplex and centralized network management, PTN plays an important role in a carrier network. SDN is developing quickly, having the characters of intel-controlling, centralized controlling and source-opened. Based on the characters, the necessity of the introduction SDN to PTN and application scenarios of base station and private line were discussed. Technical requirements of SPTN were proposed and the basic functions of SDN with the result of SPTN testbed in Shanghai CMCC were implied. Finally, the evolution road of transferred layer and controller layer in carrier network after the introduction of SDN was discussed.